The role of public health nurses in risk factor modification within a high-risk cardiovascular disease population in Ireland – a qualitative analysis. (1st October 2019) - Heery, Sheila; Gibson, Irene; Dunne, Denise; Flaherty, Gerard
Abstract: Background/aims: Health promotion for cardiovascular disease risk factors management is essential to secondary prevention of cardiovascular disease events. In Ireland, post-cardiac rehabilitation patients are discharged into the care of community public health nurses, who have a health promotion role. Little is known of the public health nurses' perceptions or knowledge surrounding their role in cardiovascular disease risk factor management. Underpinned by a constructivist viewpoint, this study aims to generate empirical evidence on the phenomenon directly from public health nurses' encounters within the context of the current health service. Methods: This qualitative cross-sectional analysis involved face-to-face, semi-structured interviews with a purposeful sample of 17 public health nurses. Interviews were audio-recorded, transcribed, subjected to thematic content analysis and subsequently reported incorporating verbatim quotes. Results: A significant gap exists between evidence-based guidelines for cardiovascular disease prevention and current practices. Variations in public health nurses' training, experience and knowledge result in inconsistent practices, and public health nurses feel this is specialised area for which they are not equipped. The changing public health nurse role and increasing workloads result in prioritisation of other nursing duties over health promotion. Ineffective systems for care delivery and a lack of community-based rehabilitation programmes also negatively impact on secondary prevention practices. Conclusions: Findings support the need to develop a community cardiovascular disease specialist role to effectively support ongoing cardiovascular disease risk factor management. Evaluation of the mechanisms of current service delivery is required to ensure a quality-assured equitable service, in line with community needs and current evidence-based guidelines for practice. A quantitative triangulation study is recommended.